From Playing With Sounds in English to the Development of Phonological Awareness - Lucija Čok; Anita Brčaninović (University of Maribor Press, 2015)
For the last few decades we have witnessed an increased interest in introducing foreign languages at early stages of education. The introduction of a foreign language at pre-school level may occur in an integrated manner or in the form of additional activities which is also reflected in the pre-school curriculum. However, in both cases, special attention should be given to the development of listening skills, especially to phonological awareness. This paper presents a model for developing phonological awareness skills in learning English as a foreign language which can be adapted for different types of pre-school programmes and other foreign languages. The implementation of the outlined activities may facilitate children's literacy development both in their first and foreign language.